Planning & Scheduling In A Multi-Site Production In A Supply Chain Management Environment - Heah, Whey Seen (2005)
This thesis propose the development of a prototype software system as an approach to collaborate decision - making between two facilities and introducing information visibility into the supply chain. Mathematical modelling approach was used to develop Aggregate Production Planning (APP) and Master production Schedule (MPS). The APP was developed as a linear programming problem in which the developed model is used to minimize total costs of production, inventory , backorders, sub-contracting, and workforce at the aggregate level.